Physical and chemical modification of starches: A review. Issue 12 (13th August 2017) - Zia-ud-Din,; Xiong, Hanguo; Fei, Peng
ABSTRACT: The development of green material in the last decade has been increased, which tends to reduce the impact of humans on the environment. Starch as an agro-sourced polymer has become very popular recently due to its characteristics, such as wide availability, low cost, and total compostability without toxic residues. Starch is the most abundant organic compound found in nature after cellulose. Starches are inherently unsuitable for most applications and, therefore, must be modified physically and/or chemically to enhance their positive attributes and/or to minimize their defects. Modification of starches is generally carried out by using physical methods that are simple and inexpensive due to the absence of chemical agents. However, chemical modification involves the exploitation of hydroxyl group present in the starches that brings about the desired results for the utilization of starches for specific applications. All these techniques have the tendency to produce starches with altered physicochemical properties and modified structural attributes for various food and nonfood applications. This paper reviews the recent knowledge and developments using physical modification methods, some chemical modification methods, and a combination of both to produce a novel molecule with substantial applications, in food industry along with future perspectives.